A Chronic Lack of Perceived Personal Control Increases Women and Men's Self-Reported Preference for High-Status Characteristics When Selecting Romantic Partners in Simulated Dating Situations. Issue 7 (September 2021) - Lammers, Joris; Imhoff, Roland
The question what people desire in their romantic partner has hitherto been dominated by a focus on gender. It has been repeatedly found that, when asked what they find important in selecting a partner, women indicate that they find status more important compared to men. Across five studies, we move beyond gender and base ourselves on general theories of control deprivation to test the effect of differences in perceived personal control on stated partner preferences. We find that low-control people—both women and men—value characteristics associated with status more in romantic partners at the expense of other desirable traits (Study 1a and 1b). Furthermore, in simulated dating settings, low-control people make corresponding dating choices and prefer hypothetical high-status partners over low- (Study 2a) or average-status partners (Study 2b). Our final study suggests a beneficial aspect: Thoughts of dating a high-status partner can repair low-control people's feelings of control (Study 3).